Constructivist Principles in Arabic Reading Instruction: An Analysis of the Fathul Kutub Program in an Islamic Boarding School - Nisa Ainul Itsna,; Agus Yasin,; Najma Ulayya Alfany, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines how constructivist learning principles are manifested in Arabic reading instruction through the Fathul Kutub program in an Islamic boarding school and explores the learning processes that characterize studentsâ€™ engagement with Arabic texts. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews with students and teachers, and document analysis. The findings reveal that Arabic reading instruction in the Fathul Kutub program is characterized by active student engagement, gradual meaning construction, and facilitated learning interactions. Text comprehension does not emerge instantly but develops through a sequence of independent reading, peer discussion, and guided clarification. Teachers play a facilitative role by prompting studentsâ€™ thinking and supporting meaning-making rather than providing direct explanations. The study highlights Arabic reading instruction as a learning process shaped by interaction among learners, texts, and pedagogical practices. Rather than evaluating program effectiveness, this study contributes conceptually by emphasizing a process-oriented understanding of qirÄâ€™ah instruction within a pesantren context